Spacial distribution of fertigated coffee root system - Marcelo Rossi Vicente; Everardo Chartuni Mantovani; André Luís Teixeira Fernandes; Júlio César Lima Neves; Edmilson Marques Figueredo; Fábio Teixeira Delazari (Ciência e Agrotecnologia)
ABSTRACT The development of coffee plant root system changes when subjected to drip irrigation and fertigation. This work aimed to evaluate the effects of different levels of fertigation on the development of coffee root system by drip irrigation in western Bahia. The experiment was carried out with Catuaí Vermelho IAC 144 coffee plants, of about 3.5 years of age, in the “Café do Rio Branco” farm, located in Barreiras - BA, and consisted of a complete randomized blocks design with 3 replicates. Treatments consisted of three levels of nitrogen and potassium fertilization (900/800, 600/500 and 300/250 kg ha-1 year-1 N and K2O), weekly distributed, by means of fertigation, throughout the process. After the fourth harvest, coffee root system was evaluated, and root length density (RLD) and root density (RD) were determined at different sampled layers. The highest root concentration, root length density (RLD), and root density (RD) were observed in the superficial layers of soil (0-20 cm), and under the dripline (30 and 70 cm from the orthotropic branch). Results showed that the lower the N and K2O levels, the higher was the development (RLD and RD) of the coffee root system.